A Novel Mutually Perpendicular Bicyclo-Shape Tetranuclear Complex Constructed from 2,3-Dihydroxy butanedioic Acid with Pisces Mode - Jiang, L.; Yang, B.Q.; Feng, G.D. (Asian Journal of Chemistry, 2014)
A new complex [Ni4(dhbd)4·8H2O]·13H2O (1) (H4dhbd = 2,3-dihydroxy butanedioic acid) has been synthesized and its structure (C16H16O45Ni4, Mr = 1163.13) was determined by single-crystal X-ray diffraction analysis. The crystal belongs to the monoclinic system, space group P21/c with a = 13.700(5), b = 17.143(5), c = 18.599(5) Å, b = 96.786(5), V = 4338(2) Å3, Z = 4, Dc = 1.781 g/cm3, μ(MoKa) = 1.839 mm-1, F(000) = 2336, S = 1.025, the final R = 0.0524 and wR = 0.1390 for 9257 reflections with I > 2s(I). The centrosymmetric nickel complex contains a tetranuclear in which four distorted octahedral Ni(II) centers are bridged by the carboxylic oxygen atoms and the hydroxy oxygen atoms of the four 2,3-dihydroxy butanedioic acid with the Pisces mode, featuring a novel mutually perpendicular bicyclo structure. The complex units are further linked to form three-dimentional supramolecular structure via the hydrogen bonds between the coordinate water molecules and the plentiful free water molecules. The elemental analysis and optical properties for the complex have been studied.